Pengoptimalisasian Peningkatan Ekonomi Keluarga untuk Mengatasi Stunting Masyarakat di Desa Tlogotirto - Amalia, Rezky Martha; Alfa Faridh Suni; Hanela Nur Aini; Dika Fitriyani; Santi Krisbanowati (Jurnal Bina Desa, 2025)
Empowering human resources at the village level, the country's first central point, is key to improving the quality of life and welfare of the community. However, there is an important issue that hinders stunting, which affects children's growth and development, thus affecting learning ability and productivity. Tlogotirto Village, Gabus Subdistrict, Grobogan, Central Java is one of the areas with a concerning stunting rate. In addition, this village is quite fertile with various natural potentials, including agricultural products, livestock, and water sources. However, community awareness of their potential is still low, which has an impact on the family economy. If this continues to happen, the handling of stunting cannot be done optimally, even though it is supported by government programs. For this reason, UNNES Giat 9 participants in Tlogotirto Village planned various programs including "Socialization of Entrepreneurship & Development of Selling Value Products, Mapping the Location of MSMEs Through Google Maps, Utilization of Used Cooking Oil Waste, Corn Cob Waste into Briquettes, and 3R Hazardous Waste Management".